Development Without Industrialization? Household Well-Being and Premature Deindustrialization. Issue 3 (3rd July 2019) - Greenstein, Joshua
Abstract: The effect of premature deindustrialization on the distribution of gains from growth has thus far been understudied. Using census data from eleven countries spanning five decades and shift-share analysis, I find evidence of persistent gaps in multidimensional well-being in household categories defined by employment type and urban/rural location, and a cross-country pattern of less improvement due to expansion of industrial employment over time, without adequate replacement. Taken together, these results provide evidence for a negative relationship between improvements in household well-being and premature deindustrialization on both an individual country case and in a cross-country sample.